The skills of recognizing the coherence in my beautiful language books for the upper primary stage in the Kingdom of Saudi Arabia - Al - Amarneh, Emad Farouk Mohammed (Journal of Educational and Psychological Sciences, 2018)
The study aimed at identifying the interconnectivity skills in the reading texts available in my beautiful language books, showing their relative weight, knowing the percentage of exercises and questions assigned to each method of linking the ideas in the reading text (linking by reference, linking to tools, linking to deletion and semantic linking). To achieve the objectives of the study, the researcher used the descriptive analytical method by analyzing these books. The study concluded that the fourth grade book consisted of (836) skill, the fifth grade book (1289) skill, the sixth grade book (1598) skill, and the total repetition of link linking skill (1963) (526) times, and semantic bonding (342) times. The study recommended the need to pay attention to the gradual in the training of students and teach them the various linkage skills, and work to achieve balance between the skills of linking in the books of reading and activities and exercises to achieve better learning for students.
Keywords: interconnection skills; Arabic language books; content analysis; the primary stage